New opportunities of medical and psychological rehabilitation of patients with schizophrenia - Kozhyna, Hanna; Markova, Marianna; Korovina, Liliia; Kryshtal, Valentine (Journal of Education, Health and Sport, 2016)
142 female patients, aged 18 – 35 y. o. with diagnosis of schizophrenia have been comprehensively examined in the period of stabilization. The integrative model of psychoeducational work which includes application of various information modules, techniques of cognitive-behavioral therapy, training effects, problem-oriented discussions, and family psychotherapy was offered. The psychoeducation was determined to be superior over conventional complex treatment intended for the reduction of negative symptoms, productive symptoms and general psychopathological symptoms of schizophrenia patients. It is supported by dynamic analysis of the clinical disturbances and psychopathological ones on the PANSS. The improvement of psychosocial functioning and quality of life of the patients under study who participated in the psychoeducational activities was determined. It is proved that psychoeducation not only increases the amount of knowledge intensifies confidence in the fight against the disease, but solves the problem of social reintegration of the patient.